Observation of in‐situ reciprocal lattice evolution of AlGaN/InGaN on Si (111) through GaN and AlN interlayers by RHEED and reflectance. Issue 5 (17th February 2016) - Bag, Ankush; Das, Subhashis; Biswas, Dhrubes
Abstract: Due to the wave‐particle duality of high energy electron beam, RHEED describes a thin film surface through the interaction of reciprocal lattice rod (RLR) of the film. The RLR spacing of the crystal has been computed using RHEED streak spacing on a fluorescent screen. Present evolution study of RLR spacing has been performed for AlGaN/InGaN heterostructure on thick GaN buffer layer during plasma‐assisted molecular beam epitaxy. Effect of composition, strain and temperature on the crystal has been identified as the function of lattice spacing during the growth. The calibrated reflectivity of LED signal has also been employed to map the thickness of different growing epilayers. RLR spacing decreases for interlayer GaN as compared to AlN. Initially, the RLR spacing of GaN buffer decreases more as compared to interlayer GaN owing to its increased growth temperature after the interlayer AlN. The RLR spacing of GaN again gradually increases with decrement of growth temperature up to the InGaN channel layer. The InGaN RLR spacing decreases again which attributes to the relaxation of InGaN on GaN. Additionally, AlGaN reveals strained state to InGaN in combination with effect of high growth temperature. The phenomena result in additional decrement of lattice distance in reciprocal space. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)